Determine the Carrying Capacity of the Tourism and Recreational Range of Natural Areas of Mashhad Metropolis along the Urban and Sustainable Urban Planning - Atefe Moradi (تحقيقات جغرافيايی, 2019)
Aims & Backgrounds: Today, the concept of capacity utilizing the maximum number of users who use a natural or recreational area at a given time without changing disturbance in the environment is widely used in urban management and planning. The purpose of this study is to determine the recreational range and tourism capacity in Mashhad area. Methodology: The research is of a practical nature and data is collected through library and field studies. Initially, 7475 hectares of the area were selected as useful and usable areas for users through the registration of ground points and the preparation of a land use map using the GIS tool. In the next step, through computational formulas, three types of physical, actual and effective physical capacity were estimated. Five limiting factors were used as coefficients in calculating the actual carrying capacity of the study site and to calculate the effective carrying capacity, managerial parameters were used. researcher-made questionnaire (Likert spectrum) was also provided to users with a record (384 people) in order to score the site management capability parameters. Findings: Among the managerial factors, the highest points belonged to grocery stores (4.8) and the lowest points belonged to the regional relief system (1.2). Finally, the carrying capacity of physical, actual, and effective related to the study area was estimated to be 89700000, 1829880, and 969836, person per day respectively which shows a physical carrying capacity was much more than actual carrying capacity. Conclusion: In general, the area accepts a significant number of users for recreational and sports activities. On the other hand, the area has considerable spaces suitable for the design and deployment of sports and leisure facilities. However, environmental and safety priorities must also be taken into account.